Common pediatric medical procedures. Lumbar puncture (cerebrospinal fluid collection) - Kelleher, Kelly J.; American Academy of Pediatrics ([Elk Grove Village, Illinois] : American Academy of Pediatrics, 2014)
A complete review and demonstration of the procedure for lumbar puncture, including patient positioning, locating the puncture site, and puncture technique.
Presenter: Kelly J. Kelleher.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 16, 2020)
Keywords: Spine -- Puncture; Pediatrics; Documentary films; Instructional films; Nonfiction films; Internet videos; Streaming video; Short films